Analisa Kebutuhan Keamanan Sistem Jaringan dan Aplikasi Dengan Metode Square Studi Kasus PT Tawada Healthcare - Al Islami, Fahmi Rusdi; Izatie, Selviany Nuri; Destiana, Indri (JURNAL SISFOTEK GLOBAL, 2016)
Security in a system that was absolutely needed to maintain the data contained in the system . Security needs to be important when the system can be accessed many and connected to the internet. Integrity, Confidential and availability, be aspect needs to be maintained on those systems, three aspects are in the ERP system application (Enterprise, Resource, Planning) on private companies in general. Security issues in the system ERP of course corresponded to issues the base that must be filled a system security. So badly needed analysis in order to protect the data and do precautionary measures so that data not occurredin use .Hence required security management an appropriate information order to ensure the success of the implementation of a system security ERP. So we emphasises the use of method by using the method SQUARE.